Neuropeptide S receptor 1 is a nonhormonal treatment target in endometriosis - Tapmeier, TT; Rahmioglu, N; Lin, J; De Leo, B; Obendorf, M; Raveendran, M; Fischer, OM; Bafligil, C; Guo, M; Harris, RA; Hess-Stumpp, H; Laux-Biehlmann, A; et al. (American Association for the Advancement of Science, 2021)
Endometriosis is a condition where endometrial-like tissues grow outside the uterus, leading to inflammation, pain, and reduced fertility. Treatment is generally hormonal or surgical, and noninvasive, nonhormonal therapies are urgently needed. Here, Tapmeier and colleagues performed genetic analyses of human families with endometriosis and rhesus macaques that spontaneously develop endometriosis, identifying NPSR1, the gene encoding neuropeptide S receptor 1, as associated with disease. The NPSR1 inhibitor SHA 68R led to reduction of inflammatory cell infiltrate and pain in mouse models of peritoneal inflammation and endometriosis. Although further studies in nonhuman primates are needed, the findings give hope for a nonhormonal treatment for endometriosis.